Peppermint Aromatherapy and Nausea in Pregnancy - Rina Mardiyana (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aimed to analyze the effect of peppermint aromatherapy on nausea and vomiting intensity among first-trimester pregnant women. A quantitative descriptive design was applied with purposive sampling involving 30 respondents. Data were collected using the PUQE-24 observation sheet before and after intervention, and analyzed using the Wilcoxon test. Results showed a significant reduction in nausea intensity (p=0.001), shifting from moderate to mild categories. Peppermint aromatherapy was found effective in relieving nausea and vomiting symptoms, improving both physical and psychological conditions. This suggests peppermint aromatherapy as a safe complementary therapy option for pregnant women.